2015
DOI: 10.4236/ojpm.2015.54019
|View full text |Cite
|
Sign up to set email alerts
|

Grounding the Human Body during Yoga Exercise with a Grounded Yoga Mat Reduces Blood Viscosity

Abstract: Objective: Research continues to show that being connected to the earth can increase the potential of the body to scavenge free radicals. This study examined the effect of just one hour of grounding on blood viscosity while subjects participated in gentle yoga exercises designed to initiate minor inflammation. Design: In this double blind model, twenty-eight (28) subjects met at the Bowerman Sports Medicine Clinic on the campus of the University of Oregon and were grounded to the earth via contact with a groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…It means that improvements of viscosity are associated with pain control. Previous studies demonstrated similar results in support of this study [13,14]. The influence of pain on hemorheology may be association with the pain-related stress response [13].…”
Section: Discussionsupporting
confidence: 89%
“…It means that improvements of viscosity are associated with pain control. Previous studies demonstrated similar results in support of this study [13,14]. The influence of pain on hemorheology may be association with the pain-related stress response [13].…”
Section: Discussionsupporting
confidence: 89%
“…However, the current study revealed that GRD showed lower decrements in performance with respect to CMJ, maximal leg strength (MVIC), a trend for DJ coefficient and less pronounced in increase in CK when compared with UGD. The less pronounced decrease in measures of performance (strength, jump performance) and less increase in CK levels within the GRD group might be attributed toward potentially reduced blood viscosity (Chevalier et al, 2013; Brown and Chevalier, 2015), enhanced blood flow velocity, improved sleep quality (Ghaly and Teplitz, 2004) and decreased muscle damage (Brown et al, 2010; Brown et al, 2015) as it is clearly demonstrated by the blood analyses of the present study. Referring to Chevalier et al (2006); Oschman (2007), and Oschman et al (2015) the main hypothesis about earthing is based on the connection to the surface of the Earth, which is satiated with free electrons.…”
Section: Discussionsupporting
confidence: 54%
“…Actually, evidence-based research regarding the effectiveness of grounding is lacking. The narrative review of Chevalier et al (2012) included grounding studies that indicated improvements in sleep (Ghaly and Teplitz, 2004), indices of DOMS (Brown et al, 2010; Brown et al, 2015), autonomic tone (Sinatra, 2011) and reduction in blood viscosity (Chevalier et al, 2013; Brown and Chevalier, 2015). Due to the potentially reduced blood viscosity, enhanced blood flow velocity, improved sleep quality and decreased muscle damage, it is suggested that grounding could be implemented as a viable, effective recovery tool after strenuous exercise.…”
Section: Introductionmentioning
confidence: 99%
“…This property of air is known as the vertical potential gradient (VPG) of the global electric circuit (GEC) [36]. Studies have found that equalizing the electric potential between the surface and Earth and the human body (earthing) improves inflammatory markers [37, 38] and blood viscosity [39, 40]. Inflammation and blood viscosity are important factors in the pathogenesis of atherosclerosis and atherothrombosis [41, 42] and hypertension [43, 44], respectively.…”
Section: Discussionmentioning
confidence: 99%